STABILITY TESTING AND DETERMINATION OF SUN PROTECTION FACTOR (SPF) VALUE IN GEL FORMULATION COMBINING MORINGA OLEIFERA L. LEAF EXTRACT WITH CITRUS AURANTIFOLIA PEEL - Rinatha, Elsha; Ulfa, Ade Maria; Tutik, Tutik (Faculty of Pharmacy, Universitas Muslim Indonesia, 2023)
The Sun Protection Factor (SPF) is an indicator that elucidates the effectiveness of a substance as a UV protector. One of the factors that influences the SPF value is the stability of the formulation. A plant with the potential to serve as a sunscreen, exhibiting both a high SPF value and gel stability, is a combination of Moringa leaves (Moringa oleifera L.) and lime peel (Citrus aurantifolia). The objective of this study is to assess the SPF value of gel preparations containing a combination of Moringa leaves and lime peel, as well as the stability of these gel preparations before and after storage, in accordance with the requirements of SNI 16-4399-1996. Three combinations, namely 1:1 (F 1), 1:2 (F II), and 2:1 (F III), were evaluated. The method employed in this study is maceration using a solvent of 96% ethanol. The results of the physical evaluation, including spreadability, pH, and adhesion, before and after stability testing for formulations F I, F II, and F III, demonstrated no significant differences with a P-value < 0.05. This indicates that the three formulations exhibited comparable results. The highest SPF test results among the three formulations, both before and after stability testing, were observed in formula III, which exhibited an SPF value of 23.86 ± 0.19. This value falls within the ultra category, and the difference was statistically significant with a P-value < 0.05.